1999
DOI: 10.1007/pl00005348
|View full text |Cite|
|
Sign up to set email alerts
|

Involvement of capsaicin-sensitive sensory nerves in early and delayed cardioprotection induced by a brief ischaemia of the small intestine

Abstract: Early cardioprotection can be achieved by a brief ischaemia of noncardiac tissues. Our study examined whether a brief ischaemia of the small intestine induces both early and delayed cardioprotection in the rabbit and assessed the possible mechanism involved in the activation of capsaicin-sensitive sensory nerves. The plasma concentration of creatine kinase (CK) and infarct size (necrotic zone/left ventricular zone) after 30 min coronary artery occlusion and 180 min reperfusion were determined in rabbits. Infar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
56
0
3

Year Published

2003
2003
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(60 citation statements)
references
References 17 publications
1
56
0
3
Order By: Relevance
“…Supporting a neuronal pathway, studies have shown that cardioprotection can be abolished by the ganglionic blocker hexamethonium [19,20] or by pretreatment sensory nerves with capsaicin [21]. It is unclear whether the humoral mediators associated with ischemic preconditioning, which include adenosine, bradykinin, and opioids, are released into the bloodstream or locally in response to neural activation [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…Supporting a neuronal pathway, studies have shown that cardioprotection can be abolished by the ganglionic blocker hexamethonium [19,20] or by pretreatment sensory nerves with capsaicin [21]. It is unclear whether the humoral mediators associated with ischemic preconditioning, which include adenosine, bradykinin, and opioids, are released into the bloodstream or locally in response to neural activation [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…A similar type of study was conducted by Kristiansen and colleagues [169] who demonstrated that hearts excised from a rat that had been remote limb preconditioned experienced a smaller infarct size, when subjected to IRI. Other studies have investigated whether endogenous substances such as adenosine [170], bradykinin [171], opioids [172], CGRP [173], and endocannabinoids [174], are released from the remote organ during the preconditioning ischemia and are carried to the heart in the blood stream where they then activate intracellular pathways of cardioprotection. Alternatively, the endogenous mediator may activate afferent neural pathways within the remote preconditioned organ to confer cardioprotection, as is the case with adenosine, bradykinin and CGRP.…”
Section: Evidence For a Potential Humoral Factor In Ricmentioning
confidence: 99%
“…Gho and colleagues [10] demonstrated that the reduction in myocardial infarct size induced by brief ischemia and reperfusion of the anterior mesenteric artery could be reversed in the presence of the ganglion blocker, hexamethonium. The hypothesis for a neural pathway was further developed with the proposition that endogenous substances such as adenosine [170], bradykinin [171], calcitonin gene-related peptide (CGRP) [173], released by the remote preconditioned organ, stimulated afferent nerve fibres, which then relayed to efferent nerve fibres terminating on the myocardium to confer cardioprotection.…”
Section: Evidence For a Potential Neural Pathway In Ricmentioning
confidence: 99%
See 1 more Smart Citation
“…It is now apparent that protection from IPC spreads from distant organs to the heart (Pell et al, 1998;Wolfrum et al, 2002) possibly via activation of the autonomic nervous system (Gho et al, 1996;Schoemaker & Van Heijningen, 2000;Liem et al, 2002;Wolfrum et al, 2002). It is possible that the release of local triggers of IPC activates the autonomic nervous system either directly (Schoemaker & Van Heijningen, 2000;Liem et al, 2002) or via sensory nerves (Tang et al, 1999;Xiao et al, 2001;Hu et al, 2002), and transfers the signal to the myocardium or other remote tissues. Evidence exists that sympathovagal regulation might be related to the protective mechanism of IPC (Loukogeorgakis et al, 2005;Wu et al, 2005).…”
Section: Heart Rate -A Measure Of Autonomic Nervous System Activitymentioning
confidence: 99%